PEMBAGIAN HARTA WARIS KHUNTSA MUSYKIL (BANCI) - Muhammad Hafidz Abizar; Habibi Al Amin (LPPM UNHASY, 2021)
This article is result of library research with a normative legal approach. Legal materials and data were obtained from Islamic legal norms regarding inheritance and khuntsa obtained from the texts of the Qur'an and Hadith, as well as the opinions of the jurists. This thesis discusses the distribution of khuntsa inheritance based on the opinion of Imam Ali As-Shobuni and Imam Abu Hanifah. People who do not have a clear gender status, not male and not female, are called khuntsa in Islamic law. One of the problems of khuntsa is in determining the right of inheritance. The Qur'an does not clearly state the portion of khuntha inheritance. This study concludes that in the unclear gender of khuntsa, it can be determined by two things, namely first, signs of maturity and second, where does urine come from. This argument is put forward using the istidlal theory used by Imam Ali As-Shobuni and Imam Abu Hanifah. If a khuntsa has a clear gender status, then this status follows the law of inheritance Keyword : Khuntha mushkil, gender, inheritance. DAFTAR PUSTAKA Amin, H. A., Masrokhin, M., & Anwar, K. (2021). GUARDIANS CONCEPT IN QUR’AN PERSPECTIVE . SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam , 6(1), 95 - 114. https://doi.org/10.33752/sbjphi.v6i1.1642 al-Jurjany, Ali bin Muhammad. Syarhus Sayyid Syarif „ala Sirajiyah, Kairo: Farjallahu Zaky al-Kurdy al-Khatib, Muhammad Asy-Syarbiny. 1958. Mughni al-Mukhtaj, Kairo: Musthafa al-Babi al-Halaby. al-Lahim, Abdul Karim bin Muhammad. 2000. Al Faraidl. Riyadh: Al-Mamlakah Al-Arabiyah al-Mawardi, Abu al-Hasan Ali bin Muhammad bin Habib. 1994. Al-Hawi Al- Kabir, Beirut: Daar al-Kutub al-„Ilmiyyah al-Qazuni, Muhammad bin Yazid, 2000. Sunan Ibn Majah, Beirut: Darul Fikr al-Shabuni, Muhammad Ali. 1985. al-Mawarits fi al-Syari‟ah al-Islamiyyah fi Dhaui al-Kitab wa al-Sunnah, Beirut: Alim al-Kitab Basyir, Ahmad Azar. 2004. Hukum Waris Islam, Yogyakarta: UII Pres Hamid, Muhammad Muhyiddin Abdul. 2009. Panduan Waris Empat Madzhab, Jakarta: Pustaka Al-Kautsar Kementerian Wakaf dan Urusan Agama Kuwait. 1983. Al-Mausu'ah Al-FiqhiyahAl-Kuwaitiyah, Kuwait: Kementerian Wakaf dan Urusan Agama Kuwait, Komite Fakultas Syariah Universitas Al-Azhar Mesir. 2004. Hukum Waris, Penerjemah Addys Al-Dizar dan Fathurrahman, Jakarta: Senayan Abadi Publishing Nasution, Amin Husein. 2012. Hukum Kewarisan Suatu Analisis Komaratif Pemikiran Mujtahid dan Kompilasi Hukum Islam, Jakarta: PT. Raja Grafindo Persada Qudamah.Al-Imam Muwaffiquddin Abi Muhammad, Abdullah bin Ahmad. 1985. Al-Mughni fi Fiqhi Al-Imam Ahmad ibn Hanbal Asy-Syaibani. Beirut: Daar al-Fikr Thaha, Muhammad. 2007. Hukum Waris, Pembagian Warisan Berdasarkan Syariat Islam. Solo: Tiga Serangkai Wizarah At Tarbiyah wa At Ta'allum. 1996. Ilmu Al-Faraidl wa Al-Mawarits. (Riyadh: Al-Mamlakah Al-Arabiyah